Aplicação de um instrumento de avaliação do grau de depressão em universitários do interior paulista durante a graduação em enfermagem - Marques Dos Santos, Telma [UNESP]; Olivetto de Almeida, Angélica [UNESP]; Oliveira Martins, Haviley [UNESP]; Moreno, Vânia[UNESP] (Universidade Estadual de Maringa, 2003)
The undergraduates in Nursing have been subject of studies on psychic problems, as alterations in behavior interfere in their learning. The aim of this research was to identify and measure the most frequent depression symptoms among the students using Beck's Depression Inventory. Socio-demographic information about the interviewees was also collected. Ninety-nine (99) students (81.82%) participated. The socio-demographic data show women's predominance (96.97%) in average with 20 years of age; 95.96% not originally from Botucatu and family monthly income of 5 to 10 minimum wages. In the total of the sampling, 41.41% presented a certain degree of depression varying from mild to severe. The most frequent symptoms were self-accusation, irritability and fatigue. The investigation shows the need of programs that follow the students during their academic formation.
Employment of an evaluation tool about depression degree on graduate nursing university students in the infkirts of São Paulo state
Keywords: Beck's Inventory; Depression; Nursing; Students; adult; Beck Depression Inventory; behavior; Brazil; depression; disease severity; employment; fatigue; female; graduate nursing student; human; human experiment; income; irritability; male; social behavior